Comparative Review of Brucellosis in Small Domestic Ruminants - Rossetti, Carlos Alberto; Maurizio, Estefanía; Rossi, Ursula Amaranta (Frontiers in Veterinary Science, 2022)
Brucella melitensis and Brucella ovis are the primary etiological agents of brucellosis in small domestic ruminants. B. melitensis was first isolated in 1887 by David Bruce in Malta Island from spleens of four soldiers, while B. ovis was originally isolated in Australia and New Zealand in early 1950’s from ovine abortion and rams epididymitis. Today, both agents are distributed worldwide: B. melitensis remains endemic and associated with an extensive negative impact on the productivity of flocks in -some regions, and B. ovis is still present in most sheep-raising regions in the world. Despite being species of the same bacterial genus, B. melitensis and B. ovis have extensive differences in their cultural and biochemical characteristics (smooth vs. rough colonial phases, serum and CO2 dependence for in vitro growth, carbohydrate metabolism), host preference (female goat and sheep vs. rams), the outcome of infection (abortion vs. epididymitis), and their zoonotic potential. Some of these differences can be explained at the bacterial genomic level, but the role of the host genome in promoting or preventing interaction with pathogens is largely unknown. Diagnostic techniques and measures to prevent and control brucellosis in small ruminants vary, with B. melitensis having more available tools for detection and prevention than B. ovis. This review summarizes and analyzes current available information on: 1) the similarities and differences between these two etiological agents of brucellosis in small ruminants, 2) the outcomes after their interaction with different preferred hosts and current diagnostic methodologies, 3) the prevention and control measures, and 4) alerting animal producers about the disease and raise awareness in the research community for future innovative activities.